Social Media and Forced Migration: The Subversion and Subjugation of Political Life - Marlowe, Jay (2019)
As social media platforms and the associated communication technologies become increasingly available, affordable and usable, these tools effectively enable forced migrants to negotiate political life across borders. This connection provides a basis for resettled refugees to interact with their transnational networks and engage in political activities in novel ways. This article presents a digital ethnography with 15 resettled refugees living in New Zealand and the role of social media and transnational networks for the maintenance and creation of political lives. Taking a broad interpretation of how political and political life are understood, this article focuses on how power is achieved and leveraged to provide legitimacy and control. In particular, it examines how refugees practise transnational politics through social media as they navigate both the subjugation and subversion of power. These digital interactions have the potential to reconfigure and, at times collapse, the distance between the resettled “here” and the transnational “there”. This article highlights how social media facilitates political lives as an ongoing transnational phenomenon and its implications for the country of resettlement and the wider diaspora.